Health Service Satisfaction To Purchase Decision: The Dual Mediation of Customer Engagement And Word of Mouth - Roosdhani, Mohamad Rifqy; Arifin, Samsul; Ali, Ali (Ekspektra : Jurnal Bisnis dan Manajemen, 2024)
This study examines the direct impact of customer satisfaction on repurchase intention and the indirect effects mediated through customer engagement and word of mouth (WOM) at Graha Husada Jepara Hospital. Involving 227 respondents with a simple random sampling method, The findings show that both WOM and customer engagement fully mediate the relationship between customer satisfaction and repurchase intention, while customer satisfaction itself exhibits an insignificant direct correlation with repurchase intention. These findings suggest that enhancing customer engagement and utilizing WOM are critical for improving repurchase intentions, as they substantially mediate the influence of customer satisfaction. Therefore, the hospital should focus on strategies that strengthen customer relationships and communication to enhance patient retention and satisfaction.